2015
DOI: 10.7727/wimj.2015.113
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of HPV and the HPV Vaccine among Pre-adolescent Girls and their Guardians in Georgetown, Guyana

Abstract: Objectives: To examine the knowledge and perceptions of 11-year old girls and their guardians toward the human papillomavirus (HPV), HPV (mandatory) useful and meaningful way and this will positively influence the decision-making process as it pertains to HPV vaccination. The Ministry of Health in Guyana has undertaken to introduce the HPV vaccine for 11-year old girls. Thus, a study that focusses on the knowledge and perceptions of the target population would be both timely and provide helpful, scientific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…38,47 Higher percentages of agreement were found when assessing young adults' attitudes towards HPV vaccination (from 35.7 in Hungary to 82.2% in Malaysia), 25,46 although in the study by Tyrell et al most girls opposing mandatory vaccination indicated that information was limited. 47 Other studies included in this analysis investigated healthcare workers' attitudes towards childhood and adult vaccinations. In Italy, according to two studies, the majority of healthcare personnel and doctors thought that mandatory vaccination should be maintained.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…38,47 Higher percentages of agreement were found when assessing young adults' attitudes towards HPV vaccination (from 35.7 in Hungary to 82.2% in Malaysia), 25,46 although in the study by Tyrell et al most girls opposing mandatory vaccination indicated that information was limited. 47 Other studies included in this analysis investigated healthcare workers' attitudes towards childhood and adult vaccinations. In Italy, according to two studies, the majority of healthcare personnel and doctors thought that mandatory vaccination should be maintained.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 22 studies assessed knowledge, attitudes and beliefs towards vaccination programs [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (Table 1), while 9 papers, two of which presented results obtained from the same study, assessed attitudes towards the Human Papilloma Virus (HPV) vaccine in young girls specifically (Table 2). 25,26,38,[44][45][46][47]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations